Intercropping AUS rice with different seed rates of Blackgram as fodder (SAARC Journal of Agriculture, 2014)
A field experiment was conducted to explore the feasibility of blackgram fodder production in Aus rice as intercropping system at the Agronomy Field Laboratory, Bangladesh Agricultural University, Mymensingh from March to July 2009. The experiment was laid out in a randomized complete block design with three replications. The fodder crop was sown at various densities as sole crop for comparison. Growth parameters, yield components and yields were higher in sole cropping. Economic analysis reveals that intercropping systems showed better performance in terms of gross, net return and benefit cost ratio compared to sole cropping of main or fodder crop at various plant populations per unit area. Intercropping blackgram as fodder with 50 kg seed ha-1 in Aus rice row sowing of 25 cm would be the promising fodder production with minimum grain yield loss of rice with higher profit. DOI: http://dx.doi.org/10.3329/sja.v12i1.21108 SAARC J. Agri., 12(1): 9-19 (2014)